Pengaruh Tax Avoidance, Firm Size Terhadap Earnings Management Dengan Financial Performance Sebagai Pemoderasi - Arianti, Baiq Fitri (Universitas Gorontalo, 2022)
The purpose of research is to empirically prove the effect of tax avoidance and firm size as independent variables, on earnings management as the dependent variable. The study also examines the role of the financial performance in moderating the relationship between these variables. The population in this study are mining sector companies listed on the Indonesia Stock Exchange for the period 2016 to 2020 totaling 193 companies. The sample in this study amounted to 28 companies with purposive sampling method, the data that were successfully processed were 140 observations. The type of research used is descriptive quantitative research. The data analysis method uses panel data regression with the help of E-views 10 software. The results showed that tax avoidance has a positive and insignificant effect on earnings management, while firm size has a negative and significant effect on earnings management, financial performance variables cannot moderate the influence of tax avoidance and financial performance variables can moderate the influence of firm size on earnings management.